Identification of New m6A Methylation Modification Patterns and Tumor Microenvironment Infiltration Landscape that Predict Clinical Outcomes for Papillary Renal Cell Carcinoma Patients - Zheng, Bin; Cheng, Fajuan; Yao, Zhongshun; Zhang, Yiming; Cong, Zixiang; Wang, Jianwei; Niu, Zhihong; He, Wei (Frontiers in Cell and Developmental Biology, 2022)
N6-methyladenosine (m6A) is the product of the most prevalent mRNA modification in eukaryotic cells. Accumulating evidence shows that tumor microenvironment (TME) plays a pivotal role in tumor development. However, the underlying relationship between m6A modification and the TME of a papillary renal cell carcinoma (PRCC) is still unclear. To investigate the relationship between m6A modification and prognosis and immunotherapeutic efficacy for PRCC, we looked for distinct m6A modification patterns based on 23 m6A-related genes. Next, the correlation between m6A modification patterns and TME-related characteristics was investigated. Then, the intersected differentially expressed genes were selected and the scoring system, denoted as m6A score, was established to evaluate m6A modification, prognosis, and immunotherapeutic efficacy. In this study, three distinct m6A expression clusters were identified. Based on the results of immune cell infiltration analysis and functional analysis, carcinogenic pathways, TME-related immune cells, and pathways were identified as well. More importantly, the established m6A score showed good value in predicting clinical outcomes according to results using external cohorts. Specifically, PRCC patients with low m6A score value showed better survival, immunotherapeutic response, and higher tumor mutation burden. Furthermore, immunohistochemistry using PRCC clinical samples from our medical center was carried out and verified our results. In conclusion, this study highlights the underlying correlation between m6A modification and the immune landscape and, hence, enhances our understanding of the TME and improved the therapeutic outlook for PRCC patients.